Using Implementation Mapping to increase uptake and use of Salud en Mis Manos: A breast and cervical cancer screening and HPV vaccination intervention for Latinas - Savas, Lara S.; Loomba, Preena; Shegog, Ross; Alaniz, Angelita; Costa, Crystal; Adlparvar, Emily; Allicock, Marlyn A.; Chenier, Roshanda; Goetz, Margaret; Markham, Christine M.; Fernandez, Maria E. (Frontiers in Public Health, 2023)
Background Despite CDC recommendations for breast and cervical cancer screening and HPV vaccination, cancer control behaviors are underutilized among low-income Latinas. Salud en Mis Manos (SEMM), adapted from Cultivando La Salud, is a community health worker- (CHW-) delivered evidence-based intervention (EBI), shown to increase breast and cervical cancer screening. Methods We used Implementation Mapping to create SEMM-Dissemination and Implementation Assistance (SEMM-DIA), a set of implementation strategies designed to support implementation and maintenance of SEMM in clinic settings. Specifically, we used Implementation Mapping's five iterative tasks to guide the use of theories and frameworks, evidence, new data, and stakeholder input to develop strategies to accelerate and improve implementation fidelity, reach, and maintenance of the SEMM intervention. The resulting implementation mapping logic model also guides the SEMM-DIA evaluation plan to assess reach, effectiveness, implementation, and maintenance. Discussion Increased use of implementation planning frameworks is necessary to accelerate the translation of EBIs to public health practice. This work demonstrates the application of Implementation Mapping to develop SEMM-DIA, providing a model for the development of other implementation strategies to support translation of evidence-based health promotion interventions into clinic settings.